Effect of small cardamom extracts on Mutans streptococci and Candida Albicans in comparison to chlorhexidine gluconate and de-ionized water (In vivo study ( - Ghada A Ibrahim; Wesal A Al - Obaidi (College of Dentistry/ University of Baghdad, 2013)
Background: Small cardamom or green cardamom is the dried fruit of the tall perennial herbaceous plant, Elettaria cardamomum Maton belonging to the family Zingiberaceae. The major use of small cardamom on world wide is for domestic culinary purpose and in medicine. This study was conducted to test the effect of small cardamom extracts on Mutans streptococci and Candida Albicans in comparison to 0.2% chlorhexidine gluconate and de-ionized water in vivo. Materials and Methods: Mutans streptococci and Candid Albicans were isolated, purified and diagnosed according to morphological characteristic and biochemical test. In this experiments, the effect of control agents and small cardamom extracts as a mouth rinses was tested on the saliva of group of volunteers to determine the level of Mutans streptococci and Candida Albicans in vivo. Also the salivary flow rate and pH were measured in vivo. Result: 10 % aqueous cardamom extracts had a highly significant antimicrobial activity against mutans streptococci after 15 min after rinsing and following times. 30 % aqueous cardamom extracts had a significant antifungal activity in vivo against Candida albican after 30 min after rinsing and following times. But still CHX is more effective than the other agents in reduction the counts of mutans streptococci and Candida Albicans. CHX 0.2% mouth rinse had the highest stimulation of salivary flow rates and pH followed by hot water cardamom mouth rinse 30% followed by cold cardamom mouth rinse 10% then de-ionized water mouth rinse. Conclusion: Cardamom extracts were effective against Mutans streptococci and Candida Albicans, but still less than CHX.